2020
DOI: 10.1021/acsami.0c11021
|View full text |Cite
|
Sign up to set email alerts
|

Design and Integration of a Layered MoS2/GaN van der Waals Heterostructure for Wide Spectral Detection and Enhanced Photoresponse

Abstract: Molybdenum disulfide (MoS2) as a typical two-dimensional (2D) transition-metal dichalcogenide exhibits great potential applications for the next-generation nanoelectronics such as photodetectors. However, most MoS2-based photodetectors hold obvious disadvantages including a narrow spectral response in the visible region, poor photoresponsivity, and slow response speed. Here, for the first time, we report the design of a two-dimensional MoS2/GaN van der Waals (vdWs) heterostructure photodetector consisting of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…Two-dimensional (2D) metal oxides can be isolated through various liquid metal-based techniques, including printing (touch, 4 squeeze, 6,37 or blade print [40][41][42][43][44][45] techniques), liquid phase growth and exfoliation (including sonication 46 and bubbling 4,47,48 methods), and surface templated growth of materials on liquid metal surfaces. 49,50 The liquid metal printing processes may also be used to assist the synthesis of heterostructures which will be discussed later in this review.…”
Section: Two-dimensional Metal Oxides From Liquid Metal-based Synthes...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two-dimensional (2D) metal oxides can be isolated through various liquid metal-based techniques, including printing (touch, 4 squeeze, 6,37 or blade print [40][41][42][43][44][45] techniques), liquid phase growth and exfoliation (including sonication 46 and bubbling 4,47,48 methods), and surface templated growth of materials on liquid metal surfaces. 49,50 The liquid metal printing processes may also be used to assist the synthesis of heterostructures which will be discussed later in this review.…”
Section: Two-dimensional Metal Oxides From Liquid Metal-based Synthes...mentioning
confidence: 99%
“…Blade coating is another alternative to the touch-and squeeze-printing techniques. 40,44 Several studies have reported different ways to perform this method, including brushing, 41 tape printing, 42,43 and roll transfer. 45 Nevertheless, they share a similarity in concept whereby a liquid metal is being moved across the substrate and leaves behind an oxide skin which is only weakly attached to the parent liquid metal.…”
Section: Two-dimensional Metal Oxides From Liquid Metal-based Synthes...mentioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83] Compared with pure NW devices, hybrid heterostructure optoelectronic devices are composed of two types of materials with different functions have a larger spectral response range, faster response speed, better sensitivity, higher optical characteristics, and emission efficiency. [84][85][86][87][88] For example, Tian et al proposed a method for combining hydrothermal growth and thermal evaporation to synthesize branched heterostructures that are composed of ZnO branches and a ZnS backbone. [89] The dendritic ZnS-ZnO heterostructure can be easily transferred to the flexible poly(ethylene terephthalate) (PET) substrate to form a nanofilm network for UV detection.…”
Section: Nw Heterojunctionmentioning
confidence: 99%
“…[ 1–3,6,9–11 ] So, the various MoS 2 ‐based heterojunction devices have been demonstrated showing enhanced detection performances and broadened spectral range in MoS 2 /Si, MoS 2 /GaAs, MoS 2 /GaN, MoS 2 /black phosphorous, etc. [ 2,6,12,13 ] Although there are many reports regarding heterojunction PDs, most of the MoS 2 ‐based devices have shown only a slight extension of wavelength coverage to approximately 1100 nm of Si materials, whereas there are strong demands on wider‐spectral PDs beyond 1300 nm for future optical communications and broadband imaging. [ 14,15 ] To extend the cutoff wavelength, the introduction of 3D bulk materials, which can provide longer wavelength absorption would be quite promising approach while considering band alignment for efficient photocarrier extraction.…”
Section: Introductionmentioning
confidence: 99%